RNA polymerase III transcriptional units are interspersed among human non-alpha-globin genes. - Duncan, C (1979)
Cloned human DNA fragments containing globin genes are transcribed in vitro to form discrete RNA species. One transcription unit is located approximately 1500 base pairs upstream from the G-gamma-globin gene. This transcript is partially homologous to a polymerase III template located approximately 1000 base pairs upstream from the delta-globin gene and to DNA located a short distance downstream from the beta-globin gene.